2012
DOI: 10.1021/ie202232j
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Selective Oxidation of Sulfides with H2O2 Catalyzed by Ionic Liquid-Based Polyoxometalate Salts

Abstract: A group of ionic liquid (IL)-based polyoxometalate (POM) salts were prepared via anion-exchange of imidazolium IL precursors tethered by different carbon chain alkyls with various Keggin POMs. The resultant imidazolium POM salts were tested as the catalysts for oxidation of sulfides with aqueous H 2 O 2 . For understanding the POM salt-catalyzed oxidation of sulfides, catalyst compositions, substrates, and reaction conditions were changed. The results show that the imidazolium POM salts are very active and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 60 publications
0
39
0
Order By: Relevance
“…28 Ionic liquids are an intriguing class of solvent that has been widely utilized for immobilisation of catalysts under homogeneous, liquid-liquid biphasic and liquid-solid (SILP) biphasic conditions, in some cases with remarkable success. 29 Recent endeavours in this area include highly selective sulfoxidations catalysed by a SILP system based on imidazolium modified SBA-15 and [MoO(O2)2(H2O)n], 30 a magnetically recoverable sulfoxidation catalyst based on magnetic nanoparticles entrapped in a tungstate-functionalised polyionic liquid, 31 an eco-friendly protocol for the oxidation of sulphides to sulfones catalysed by V2O5 in [C12mim][HSO4], 32 efficient and selective sulfoxidation catalysed by peroxotungstates immobilised on multilayer ionic liquid brushes-modified silica 33 Other recent developments include selective oxidation of sulfides with H2O2 catalysed by heterogeneous ionic liquidbased polyoxometalates, 34 selective oxidation of sulphides with a sulfoacid-hexafluorotitanate(IV) bifunctional ionic liquid, 35 ionic liquid-mediated oxidation of sulphides to sulfoxides, 36 efficient eco-friendly selective oxidation of sulphides to sulfoxides with molecular oxygen catalysed by Mn(OAc) 2 in [C12mim][NO3], 37 rapid oxidation of sulfides by themoregulated polyoxometalate based ionic liquids, 20b,38 selective and efficient desulfurization by amphiphilic polyoxometalate-based ionic liquid supported silica, 39 and heterogeneous selective sulfoxidation with polymeric ionic liquid nanogel-immobilised tungstate anions. 40 We have recently applied the concept of SILP-based technology to develop peroxotungstate-based Polymer Immobilised Ionic Liquid Phase (PIILP) oxidation catalysts in order to combine the favourable and tuneable properties of ionic liquids with the advantages of a solid porous support.…”
Section: Introductionmentioning
confidence: 99%
“…28 Ionic liquids are an intriguing class of solvent that has been widely utilized for immobilisation of catalysts under homogeneous, liquid-liquid biphasic and liquid-solid (SILP) biphasic conditions, in some cases with remarkable success. 29 Recent endeavours in this area include highly selective sulfoxidations catalysed by a SILP system based on imidazolium modified SBA-15 and [MoO(O2)2(H2O)n], 30 a magnetically recoverable sulfoxidation catalyst based on magnetic nanoparticles entrapped in a tungstate-functionalised polyionic liquid, 31 an eco-friendly protocol for the oxidation of sulphides to sulfones catalysed by V2O5 in [C12mim][HSO4], 32 efficient and selective sulfoxidation catalysed by peroxotungstates immobilised on multilayer ionic liquid brushes-modified silica 33 Other recent developments include selective oxidation of sulfides with H2O2 catalysed by heterogeneous ionic liquidbased polyoxometalates, 34 selective oxidation of sulphides with a sulfoacid-hexafluorotitanate(IV) bifunctional ionic liquid, 35 ionic liquid-mediated oxidation of sulphides to sulfoxides, 36 efficient eco-friendly selective oxidation of sulphides to sulfoxides with molecular oxygen catalysed by Mn(OAc) 2 in [C12mim][NO3], 37 rapid oxidation of sulfides by themoregulated polyoxometalate based ionic liquids, 20b,38 selective and efficient desulfurization by amphiphilic polyoxometalate-based ionic liquid supported silica, 39 and heterogeneous selective sulfoxidation with polymeric ionic liquid nanogel-immobilised tungstate anions. 40 We have recently applied the concept of SILP-based technology to develop peroxotungstate-based Polymer Immobilised Ionic Liquid Phase (PIILP) oxidation catalysts in order to combine the favourable and tuneable properties of ionic liquids with the advantages of a solid porous support.…”
Section: Introductionmentioning
confidence: 99%
“…Our initial catalyst evaluation, comparison and optimization focused on thioanisole as the benchmark substrate as this oxidation has recently been catalysed by peroxometalate-based systems immobilized on the surface of ionic liquid modified silica, 23b,c ionic liquid-based polyoxometalates salts, 28 a temperature responsive phase transfer catalyst based on a Keggin-type lacunary anions 20b as well as tungstate ions embedded in mesochannels of SBA-15 23a and poly(ionic) liquid entrapped magnetic nanoparticles. 29 A series of batch reactions were first conducted to explore the effect of the H 2 O 2 :substrate mole ratio on conversion and selectivity in acetonitrile and methanol, details of which are presented in Table 1.…”
Section: Catalyst Synthesis Batch and Recycle Studiesmentioning
confidence: 99%
“…23 Ionic liquids (ILs) are a fascinating class of solvent that have been widely embraced by the catalysis community as a method for immobilization of catalysts under homogeneous, liquid-liquid biphasic and liquid-solid (SILP) biphasic conditions. 24 Recent relevant examples include an efficient protocol for the oxidation of sulfides to sulfones catalyzed by V 2 O 5 in [C 12 mim] [HSO 4 ], 25 highly selective sulfoxidation of sulfides to sulfoxides catalysed by the bifunctional IL combination [SO 3 HC 3 py][TiF 6 ]/[C 4 py] [BF 4 ], 26 a selective catalyst-free oxidation of sulfides to sulfoxides that is faster in ionic liquid than conventional solvents, 27 and, most recently, heterogeneous selective oxidation of sulfides catalysed by ionic liquid-based polyoxometalates 28 or tungstate-based poly(ionic)liquid entrapped magnetic nanoparticles. 29 While good conversions and high selectivities have been obtained In IL media, surprisingly few recycle studies have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012 Wang et al synthesized several imidazolium polyoxometalate salts using Keggin-type polyoxometalate ions as counter-ions while varying the length of the carbon chains at the imidazolium cations. The salts provided good yields in the oxidation of sulfides with aqueous H 2 O 2 [25].…”
Section: Introductionmentioning
confidence: 99%